Anticancer Activity of Angelica dahurica Used in Traditional Chinese Medicine (TCM) against Human Breast Cancer Cells: Mechanistic Evaluation by Using an Integrated Approach of Network Pharmacology, Computational Molecular Docking and Experimental Assays - Li, Yanqiu; Zhao, Chenhui; Ren, Yanling; Xie, Liping (Indian Journal of Pharmaceutical Education and Research, 2026)
Background: Breast Cancer (BC) remains a major global health challenge, necessitating novel treatment approaches to improve therapeutic outcomes. Angelica dahurica, a traditional medicinal plant, contains phytochemicals with potential anticancer properties, offering a promising avenue for investigation. Aim: This study evaluates the anticancer potential of Angelica dahurica extract against BC by integrating in silico network pharmacology with in vitro experimental validation, focusing on the modulation of key oncogenic targets STAT3, SRC, and MAPK1. Materials and Methods: In silico, phytochemicals from Angelica dahurica were screened using the TCMSP database, with targets predicted via SwissTargetPrediction and SuperPred. BC-related targets from GeneCards were intersected using JVenn. A protein-protein interaction network was constructed with STRING, analyzed in Cytoscape, and key targets identified via cytoHubba. Molecular docking was performed using DockThor, and SRPlot assessed functional relevance. In vitro, MCF-7 (BC) and MCF-10 (normal) cell lines underwent MTT cytotoxicity, clonogenic, EdU proliferation, Annexin V/PI apoptosis, and Western blotting assays. Results: In silico screening filtered 99 phytochemicals to 13, yielding 155 unique targets based on OB≥30%, DL≥0.18, and Caco-2 filters. From 3,899 BC-related targets, 138 overlapped, with STAT3, SRC, and MAPK1 as central hubs. Docking confirmed sitogluside’s strong binding to these targets, with high-affinity binding energies. SRPlot revealed enriched pathways in proliferation and apoptosis. In vitro, the extract showed dose-dependent cytotoxicity in MCF-7 cells (40-160 μg/mL), reducing viability by up to 60%, with minimal MCF-10 toxicity. Clonogenic assays indicated 70% inhibition of colony formation, and EdU assays showed 50% reduction in DNA synthesis. Annexin V/PI staining confirmed 40% apoptosis induction. Western blotting revealed dose-dependent downregulation of STAT3, SRC, and MAPK1, with reductions up to 65%. Conclusion: Angelica dahurica extract, particularly sitogluside, effectively targets key oncogenic pathways in breast cancer, supporting its potential as a novel therapeutic agent against BC.
Keywords: Angelica dahurica; Network-Pharmacology; Breast Cancer; Gene-ontology Enrichment Analysis; Molecular Docking; Cytotoxicity